The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1098/rsos.170658
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient synthesis of [60]fullerene oxides by plasma jet

Abstract: Atmospheric pressure nonequilibrium plasma jet has been applied to the synthesis of [60]fullerene oxides (C60On) for the first time. C60O and C60O2 were produced and isolated in high yields up to 44% and 21%, respectively. The structural assignment of C60O was confirmed by comparison with the reported spectroscopic data. Theoretical calculations of 13C NMR chemical shifts for eight isomers of C60O2 were performed and compared with the experimental data to assign the most possible structure for the obtained C60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…As a result of the new possibilities of atmospheric pressure plasma-liquid systems, plasma-driven organic synthesis is receiving renewed attention and recent studies have demonstrated, for example, plasma-initiated radical chemistry, oxidation of fullerenes and environmentally friendly production of peroxynitrite. [14][15][16] Of particular interest, are novel synthetic processes that eliminate waste streams. This is the case because conventional manufacturing of chemical compounds typically generates large amounts of waste.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the new possibilities of atmospheric pressure plasma-liquid systems, plasma-driven organic synthesis is receiving renewed attention and recent studies have demonstrated, for example, plasma-initiated radical chemistry, oxidation of fullerenes and environmentally friendly production of peroxynitrite. [14][15][16] Of particular interest, are novel synthetic processes that eliminate waste streams. This is the case because conventional manufacturing of chemical compounds typically generates large amounts of waste.…”
Section: Introductionmentioning
confidence: 99%